Development Toward the Adoption of the FAO Agreement on Port State Measures to Prevent, Deter and Eliminate Illegal, Unreported and Unregulated Fishing - Agoes, Etty R. (UI Scholars Hub, 2011)
On November 25, 2009, during its governing conference in Rome, the Foodand Agriculture Organization of the United Nations (FAO) approved a newtreaty aimed at closing fishing ports to ships involved in illegal, unreported,and unregulated (IUU) fishing. This article is designed to give an illustrationon the development of efforts by the international community as a responseto the problems brought by IUU fishing practices. It will start with adescription on the background, then on port state control. It will then befollowed with an anlysis of the international legal basis for port statejurisdiction. The next part will discuss the case of IUU fishing, and finally onthe FAO Model Scheme on Port State Measures to Combat IUU Fishing, andthe recent Agreement on Port State Measures.